An educational intervention to implement skin-to-skin contact and early breastfeeding in a rural hospital in Mexico - Luis Fernando Sanchez-Espino; Gregorio Zuniga-Villanueva; Jose Luis Ramirez-GarciaLuna (BMC, 2019)
Abstract Background Early skin-to-skin contact promotes infant physiologic stability, provides warmth and makes breast milk readily available. Despite the known benefits of early skin-to-skin contact, this practice is not included within standard care in the Mexican public healthcare system. After birth, newborns are usually taken to an incubator in the nursery where they transition to extrauterine life and receive either dextrose 5% or infant formula for their first feed. The aim of this study was to assess if a dual educational intervention in a rural hospital in Mexico could modify current practice and accomplish early skin-to-skin contact and early breastfeeding. Methods A two-step educational intervention was designed. The first step was to educate the labor and birthing staff of the hospital, and the second step was to educate all pregnant women with uncomplicated pregnancies at 36 weeks' gestation. The educational intervention explored the benefits, implications and steps of early skin-to-skin contact and early breastfeeding. All births were registered for the three month period following the intervention. The time of onset of skin-to-skin (SSC) contact, its duration and time of initiation of breastfeeding were recorded and analyzed using ANOVA testing. Results A total of 142 births met our inclusion criteria, from those, 77% (n = 109) received skin-to-skin contact and early breastfeeding. The average time of initiation of skin-to-skin contact in the first and last month of the study was 18.5 (± 2.2) and 9.6 (± 2.2) minutes of life, respectively (p < 0.001). The average duration of SSC in the first and last month was 22 (± 10.9) and 40.9 (± 17.4) minutes, respectively (p < 0.001). The average time of onset of breastfeeding in the first and last month was 48.9 (± 15) and 34.4 (± 16.7) minutes of life, respectively (p < 0.001). Conclusions A simple and low-cost educational intervention achieved the inclusion of skin-to-skin contact and early breastfeeding as part of standard care in a rural hospital. Further studies could replicate our intervention in similar settings to test the generalizability of the findings.